2020
DOI: 10.3389/fchem.2020.00172
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Boron Doped TiO2 as an Efficient Visible Light-Driven Photocatalyst for Organic Dye Degradation With High Reusability

Abstract: No visible light activity is the bottle neck for wide application of TiO 2 , and Boron doping is one of the effective way to broaden the adsorption edge of TiO 2 . In this study, several Boron doped TiO 2 materials were prepared via a facile co-precipitation and calcination process. The B doping amounts were optimized by the degradation of rhodamine B (Rh B) under visible light irradiation, which indicated that when the mass fraction of boron is 6% (denoted as 6B-TiO 2 ), the boron doped TiO 2 materials exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…To overcome these shortcomings, a variety of techniques have been employed on ZnO and TiO 2 . These include metal and nonmetal doping, noble metal loading, dye sensitization, and semiconductor coupling [11][12][13][14][15][16]. Panwar et al [17] fabricated Gd-ZnO/TiO 2 nanocomposites via the sol-gel method and studied the photocatalytic degradation of organic dyes under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, a variety of techniques have been employed on ZnO and TiO 2 . These include metal and nonmetal doping, noble metal loading, dye sensitization, and semiconductor coupling [11][12][13][14][15][16]. Panwar et al [17] fabricated Gd-ZnO/TiO 2 nanocomposites via the sol-gel method and studied the photocatalytic degradation of organic dyes under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, boron incorporation into nanostructured TiO 2 has been proposed as an alternative to overcome some of the drawbacks mentioned above. A potential benefit of the presence of boron is the creation of electronic levels that could hinder the recombination of the electron–hole pairs. ,− Density functional theory calculations suggest that the occupation of interstitial sites or O substitution are more energetically favorable than substitution of Ti by B atoms . It has been reported that the addition of boron to TiO 2 sol–gel precursors generally leads to interstitial B-doping, together with the formation of B 2 O 3 on the surface of the TiO 2 particles. ,,, Some studies have also shown that surface boron species can introduce residual charge, which can increase the number of surface OH groups, being them correlated with the incorporated B. , …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a photoactivity improvement upon B doping of TiO 2 , ,− but the interpretation is still controversial, especially regarding the local structure around the boron impurity and the electronic effects of the dopant species. ,, Zhang et al reported highly efficient photocatalysts consisting of B-TiO 2 (3.5 at. B %) for gas phase degradation of benzene under UV–vis light, which are more active than the commercial TiO 2 -P25.…”
Section: Introductionmentioning
confidence: 99%
“…The titanium oxide (TiO2) has an environmentally friendly nature, low cost, and excellent photocatalytic activity [6]. Moreover, TiO2 has chemical stability, high redox reactivity, high thermal resistance, and low toxicity [7,8]. Despite all the superior features about TiO2, the use of visible light is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the superior features about TiO2, the use of visible light is limited. This material only uses about 45 % solar energy of visible light and ~4 % of ultraviolet light [7]. Concerning this drawback, doping TiO2 with metal and non-metal elements can enhance visible light absorption that can increase photocatalytic activity [9,10].…”
Section: Introductionmentioning
confidence: 99%